2016
DOI: 10.3390/nu8050289
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Low-Fat Diets Differing in Protein and Carbohydrate Content on Cardiometabolic Risk Factors during Weight Loss and Weight Maintenance in Obese Adults with Type 2 Diabetes

Abstract: Despite evidence for the benefits of higher-protein (HP) diets in weight loss, their role in type 2 diabetes mellitus (T2DM) management and weight maintenance is not clear. This randomised study compared the effects of a HP diet (38% carbohydrate, 30% protein, 29% fat) to a isocaloric higher-carbohydrate diet (HC: 53%:21%:23%) on cardiometabolic risk factors for 12 weeks in energy restriction (~30% reduction) followed by 12 weeks of energy balance whilst performing regular exercise. Outcomes were measured at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 35 publications
4
46
0
Order By: Relevance
“…Figure 1 shows the network diagram of direct comparison for SBP with the number of studies reflected by the size of the edges, and the number of patients reflected by the size of the nodes. The comparisons with the largest amount of trials include: HP vs. LF (Brinkworth et al 2004a;Brinkworth et al 2004b;Campbell and Meckling 2012;Dalle Grave et al 2013;Dansinger et al 2005;Delbridge et al 2009;Kim et al 2014;Krebs et al 2012;Luger et al 2013;Tang et al 2013;Watson et al 2016;Wycherley et al 2010) (n D 12), low-sodium vs. control (Alli et al 1992;Chalmers et al 1986;Costa et al 1981;Dodson et al 1989;Erwteman et al 1984;Jula and Karanko 1994;Makela et al 2008;Silman et al 1983;Whelton 1997;Whelton et al 1998) (n D 10), LF vs. control (Anderssen et al 1995;Andrews et al 2011;Ard et al 2016;Coppell et al 2010;Gordon, Scott, and Levine 1997;Heilbronn, Noakes, and Clifton 1999;Rock et al 2014;Uusitupa et al 1993;Watkins et al 2003) (n D 9), and LC vs. LF dietary approaches (Daly et al 2006;Guldbrand et al 2012;Iqbal et al 2010;Liu et al 2013;Stern et al 2004;Tay et al 2008;…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the network diagram of direct comparison for SBP with the number of studies reflected by the size of the edges, and the number of patients reflected by the size of the nodes. The comparisons with the largest amount of trials include: HP vs. LF (Brinkworth et al 2004a;Brinkworth et al 2004b;Campbell and Meckling 2012;Dalle Grave et al 2013;Dansinger et al 2005;Delbridge et al 2009;Kim et al 2014;Krebs et al 2012;Luger et al 2013;Tang et al 2013;Watson et al 2016;Wycherley et al 2010) (n D 12), low-sodium vs. control (Alli et al 1992;Chalmers et al 1986;Costa et al 1981;Dodson et al 1989;Erwteman et al 1984;Jula and Karanko 1994;Makela et al 2008;Silman et al 1983;Whelton 1997;Whelton et al 1998) (n D 10), LF vs. control (Anderssen et al 1995;Andrews et al 2011;Ard et al 2016;Coppell et al 2010;Gordon, Scott, and Levine 1997;Heilbronn, Noakes, and Clifton 1999;Rock et al 2014;Uusitupa et al 1993;Watkins et al 2003) (n D 9), and LC vs. LF dietary approaches (Daly et al 2006;Guldbrand et al 2012;Iqbal et al 2010;Liu et al 2013;Stern et al 2004;Tay et al 2008;…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis should be formally tested in a well‐designed trial. Since the publication of the two meta‐analyses, more randomized trials have reported . In general, their results are consistent with those of the meta‐analyses: a higher proportion of protein in the diet appears to have little effect on glycaemia independent of weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…Of the macronutrient changes, only reduced carbohydrate intake was significantly associated with reductions in fasting glucose concentrations in this trial suggesting an immediate physiological response to dietary carbohydrate restriction. However, a recent study in individuals with type 2 diabetes demonstrated that 12 weeks of significant calorie restriction (1450 calories per day) and enhanced exercise reduced IR by nearly 40% regardless of the macronutrient composition of the diet [ 7 ]. Yet, when calorie intake increased to 1700 calories per day for weight maintenance (weeks 13 to 24), there were no further reductions in IR even with continued enhanced exercise.…”
Section: Introductionmentioning
confidence: 99%